English Travellers abroad, 1604-1667: Their Influence on English Society and Politics - Stoye, J.W. (Octagon, 1968)
What were the experiences of English travelers who toured Western Europe in the seventeenth century? What influence did Continental travel have on English society and politics? This book by John Stoye allows us to accompany the seventeenth-century British traveler on his journeys into France, Italy, Spain, and the Netherlands. It is a travel book for historians and a piece of history for travellers.Using a vast range of contemporary sources, Stoye describes the journeys of both famous figures and of more obscure travelers, relating common itineraries and the conditions of travel. He evokes the different types of travelers and their motives and interests―young men on the Grand Tour with their tutors in tow, diplomats, soldiers, religious refugees, and merchants. Stoye considers what the travellers brought home with them, from actual books and pictures to impressions of architecture and music to new ways of looking at the world. He traces through letters and diaries how travel affected the taste, education, and politics of the upper classes of society. This book, first published in 1952, is widely considered a classic.
Keywords: 17th Century (1601-1700); Travel; Grand Tour; Cultural history; Politics; Influence; United Kingdom; Europe